Peningkatan keterampilan passing bawah bola voli melalui pemanfaatan alat bantu papan spalk - Saputra, Andika Perdana; Mulyadi, Agus; Purwana, Heri (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam 45, 2024)
This research is motivated by the common understanding that coaching and training in physical education and sports often emphasize physical abilities and technical skills, with minimal attention to psychological aspects. However, the conceptual framework for optimal achievement should encompass all supporting aspects simultaneously, including physical, technical, tactical, and mental dimensions. Therefore, this study aims to evaluate whether training using a spiking board tool influences the skills and abilities of underhand volleyball passing. The study involved 21 students from SDN 4 Bayasari, Jatinagara, as the input variable. The training method employed was underhand volleyball passing exercises using a spiking board. The research utilized the Classroom Action Research approach, consisting of two cycles and four stages: planning, implementation, observation, and reflection.The research findings indicate that the training method with the spiking board significantly enhances underhand volleyball passing skills. In the second cycle, there was a notable increase in skills, reaching 90.48%, while the ability to execute underhand volleyball passing improved to 85.71%. These results suggest that the use of the spiking board as a training aid has a positive impact on the development of students' skills and abilities in volleyball.